The effect of merger anticipation on bidder and target firm announcement period returns - Cornett, Marcia Millon; Tanyeri, Başak; Tehranian, Hassan (Journal of Corporate Finance, 2011)
This paper examines investors' anticipation of bidder and target merger candidacy and if investor anticipations about candidacy affect the distribution of value between bidder and target firm shareholders. We find that bidder firms can be predicted more accurately than target firms. To investigate how merger announcement period returns are distributed among bidder and target shareholders, we control for different degrees of predictability in bidder and target selection and find that the difference between bidder and target firm three-day cumulative abnormal returns around a merger announcement decreases significantly. Thus, the evidence supports the hypothesis that the asymmetry in investor anticipations about merger candidacy causes disparity in bidder and target firm announcement period abnormal returns.